2014
DOI: 10.1038/cr.2014.74
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome profiling reveals sequence-independent post-initiation pausing as a signature of translation

Abstract: The journey of a newly synthesized polypeptide starts in the peptidyltransferase center of the ribosome, from where it traverses the exit tunnel. The interior of the ribosome exit tunnel is neither straight nor smooth. How the ribosome dynamics in vivo is influenced by the exit tunnel is poorly understood. Genome-wide ribosome profiling in mammalian cells reveals elevated ribosome density at the start codon and surprisingly the downstream 5th codon position as well. We found that the highly focused ribosomal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 32 publications
7
51
1
Order By: Relevance
“…The fact that SMN-primed ribosomes are located within the first codons of SMNspecific transcripts suggests a highly specific, local function for this defined subpopulation of ribosomes. A general enrichment of signal at the beginning of the coding sequence is a property shared with ribosomes in general, as previously observed in several studies using classical ribosome profiling (51)(52)(53). Nonetheless, in the case of SMN-primed ribosomes, the signal is almost exclusively located at the very beginning (i.e.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The fact that SMN-primed ribosomes are located within the first codons of SMNspecific transcripts suggests a highly specific, local function for this defined subpopulation of ribosomes. A general enrichment of signal at the beginning of the coding sequence is a property shared with ribosomes in general, as previously observed in several studies using classical ribosome profiling (51)(52)(53). Nonetheless, in the case of SMN-primed ribosomes, the signal is almost exclusively located at the very beginning (i.e.…”
Section: Discussionsupporting
confidence: 75%
“…within the first 5 codons), and SMN-specific transcripts show a definite enrichment in rare codons in those positions. Importantly, it has been observed that a ribosome-pause at these very first codons acts as a translational-checkpoint to ensure productive ribosome elongation and protein synthesis (53). Accordingly, SMN binds to the elongation factor eEF1A (50) and we found that it is required for productive translation in vitro.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…We have also shown the existence of a generalized translational elongation pause at the 7 th amino acid (Figures 4C and S4E), which is consistent with an interaction of the nascent peptide with the ribosome exit tunnel (Ito and Chiba, 2013; Wilson and Beckmann, 2011). Recently, the existence of a sequence-independent post-initiation pause at the 5 th amino acid has been reported (Han et al, 2014). The authors suggested that this pause is caused by the interaction of the nascent peptide with the ribosome exit tunnel ( i.e.…”
Section: Discussionmentioning
confidence: 99%
“…repeat 1 and repeat 2, RiboSeq CHX mock 1 h in S4 Fig). In contrast to [24], we believe that the clear spike four codons downstream of the initiation peak is an artefact of ligation bias (and potentially also other biases): every read mapping to this position begins with 5 0 -AUG (thus compounding any ligation preferences), whereas reads that map to the initiation peak have different 5 0 and 3 0 ends in different mRNAs (thus averaging out any ligation preferences). For 30-nt reads, a trough was also apparent four codons upstream of the termination peak (S5 Fig); this corresponds to reads that all end in UAG-3 0 , UAA-3 0 or UGA-3 0 , and again is likely to be an artefact of ligation bias.…”
Section: Assessment Of Data Qualitymentioning
confidence: 92%